The creation of a hybrid arbitration from a pathological arbitration clause - CHAN, Darius (Institutional Knowledge at Singapore Management University, 2013)
In HKL Group Co Ltd v Rizq International Holdings Pte Ltd [2013] SGHCR 5, the Singapore High Court was asked to grant a stay of proceedings in favour of arbitration under the International Arbitration Act. One of the two issues in that case was that the arbitration clause suffered a drafting defect.